Royal Jelly: Chemistry, Storage and Bioactivities - Maghsoudlou, Atefe; Mahoonak, Alireza Sadeghi; Mohebodini, Hossein; Toldra, Fidel (Journal of Apicultural Science, 2019)
Royal jelly (RJ) has been known for centuries, but in the last 5-6 decades its systematic production and consumption has increased. RJ is secreted by the hypopharyngeal and mandibular glands of worker honeybees ( ). This thick and milky substance contains water, proteins, carbohydrates, lipids, minerals, vitamins and such bio-active compounds as acetylcholine, peptides, the hormones testosterone, progesterone, prolactin, estradiol, (hydroxydecanoic acid) (HAD), adenosine monophosphate (AMP)-N1Oxide, polyphenols, flavonoids and adenosine. Because of its bioactive compounds, RJ can be considered as a functional and nutraceutical food. The main goal of this review is to summarize and update its physicochemical properties, bio-active ingredients, storage stability and shelf life. The functional properties are antioxidative activity, insulin-like action, improvement against diabetes, liver protection, antitumoral action, neurotrophic action, antibiotic effect, anti-inflammatory action and wound healing, hypotensive effect and blood regulatory actions, anti-aging effect and skin protection, effects on the reproductive system and fertility and also fortifying, tonic action and immunomodulating and anti-alergic activity. RJ may cause allergic reactions, asthma and even fatal anaphylaxis in some humans. Therefore, RJ should be orally ingested as nutreaceutical agent or food-ingredient only after an allergy test.